Implantação de gestão da qualidade no serviço de hemoterapia em um hospital público do Estado de São Paulo - Paludetto, Nívia Maria Ortiz [UNESP] (2015)
The Assis Regional Hospital located in the city of Assis, in the countryside of the state of São Paulo, started its service to the population in 09/21/1991. It currently serves 25 cities in the region covered by the DIR VIII. The Hematology Center of the Assis Regional Hospital, as a public institution linked to the Health Department of the State of São Paulo, started as a transfusion agency in 1991 and became a Collection and transfusion unit in 2000; it accomplishes the guidelines of the National Policy for Blood and Blood Products, serving as a reference in the procedures performed. It collects about 360 blood bags monthly. It performs the processes involving: Collection, Processing, Transfusion and Blood components distribution, also assisting patients in need of cupping therapy. Transfusion services need to ensure the quality and therapeutic efficacy of the blood in Article 9 RDC 57 from December 16, 2010, which says: Every transfusion service should have a quality management system regarding the best practices of the blood production cycle and due to this, it was justified the need to implement a Quality Management System in the Collection and Transfusion Unit in Assis. The study was conducted in IV phases: During phase I we created the organizational identity politics, reviewed and built Standard Operating Procedures OP's, described macro processes and sub-processes from all areas of the blood cycle. In phase II, the audit provided situational diagnosis, and an action plan, prepared from the non-conformities found, guided the actions; at this stage, we implemented a nonconformity report, Registration Control and Petrochemicals Traceability. Phase III showed that 97.8% of TRs (Transfusion Requirements) had non-compliance as to the information filled. At this stage, four monitoring indicators were implanted in attracting donors, three in the collection, one in the production, four in the stock and 1 in the caregiver. In phase ...